Strategies of Rent Seeking during The Sukarno Period: Foreigners and Corruption, 1950–1965 - Farabi Fakih (Universitas Gadjah Mada, 2017)
This articles tries to analyze the corruption strategy that was becoming institutionalized during the Liberal Democracy (1950-1957) and Guided Democracy (1957-1965) period and how the state dealt with these challenges through managerial strategies. Corruption here is seen as a discourse that are often used by new state elite entrant to discredit old elites, especially those with connection to the financial or economic policy makers. The position of foreigners here are central because they provide opportunities for asset transfer or the creation of new assets. By looking at the financial transition from Liberal Democracy to Guided Democracy, the forms of transfer or asset production through corruption or collusion could be discerned.